Profile of Coagulation Marker and The Influence Factors in Central Nervous System Tumor - Yunni Diansari; Mediarty Syahrir; Sri Novianty Yusuf (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Brain tumors have the highest percentage of thrombosis compared to other types of malignancies. Hypercoagulation is a risk for thromboembolic events in patients with malignancy. Hypercoagulation conditions are frequently found in patients with malignancy arising from the aptitude of tumor cells to activate the coagulation system. This condition can be detected through coagulation markers in the blood. This marker is PT, APTT, INR, Fibrinogen and D-Dimer. This research is a descriptive analytic study using secondary data from medical records of patients with central nervous system (CNS) tumors. The inclusion criteria were CNS tumor patients > 18 years old and had been diagnosed with CNS tumor. Coagulation markers are recorded based on the results of the initial laboratory examination upon entering the hospital, consisting of D-Dimer, PT, APTT, Fibrinogen, INR. There were 124 research subjects, consisting of 60 men and 64 women. Most research subjects are in the age range of 40-49 years (54.8%). Hypercoagulation conditions were found in 92.74% of study subjects. The most common accompanying condition was hypertension (22.6%). There were no significant differences in the hypercoagulable conditions in groups with and without accompanying conditions. Hypercoagulation was found in most research subjects. There are no factors that influence the hypercoagulation condition in this study.